Pre-clinical evaluation of antiproteases as potential candidates for HIV-1 pre-exposure prophylaxis - Herrera, Carolina; Olejniczak, Natalia; Noël-Romas, Laura; Plummer, Frank; Burgener, Adam (Frontiers in Reproductive Health, 2022)
Previous studies on highly HIV-1-exposed, yet persistently seronegative women from the Punwami Sex Worker cohort in Kenya, have shed light on putative protective mechanisms, suggesting that mucosal immunological factors, such as antiproteases, could be mediating resistance to HIV-1 transmission in the female reproductive tract. Nine protease inhibitors were selected for this study: serpin B4, serpin A1, serpin A3, serpin C1, cystatin A, cystatin B, serpin B13, serpin B1 and α-2-macroglobulin-like-protein 1. We assessed in a pilot study, the activity of these antiproteases with cellular assays and an ex vivo HIV-1 challenge model of human ecto-cervical tissue explants. Preliminary findings with both models, cellular and tissue explants, established an order of inhibitory potency for the mucosal proteins as candidates for pre-exposure prophylaxis when mimicking pre-coital use. Combination of all antiproteases considered in this study was more active than any of the individual mucosal proteins. Furthermore, the migration of cells out of ecto-cervical explants was blocked indicating potential prevention of viral dissemination following amplification of the founder population. These findings constitute the base for further development of these mucosal protease inhibitors for prevention strategies.